Design And Analysis Of Formula Sae Vehicle Rear Upright Andcomparision Of Analytical And Software Analysis Solutions Ofprincipelstressesat Differentpoints - et. al., Sasanapuri Sandeep, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Upright is used in vehicles which connects frame or chassis and tires. Chassis is connected toupright with A-arms at the top and bottom using different types of fasteners through which theload is transmitted to it. I choose to design a FSAE(formula society of automobile engineers) caruprightbasedonthedatacollectedfromarealtimehybridformulavehicle.Uprightismodeledin Solidworks 2015 and all principle stresses and strains are found through simulation analysissoftware ANSYS 19.2. Now these solutions are compared with the analytical solutions which issolved using MATLAB software, So that we can be able to predict which one is more accurateandhowthese simulationsoftwareare beingableto solveproblemsbased ontheseconcepts.